THE RELATIONSHIP BETWEEN KNOWLEDGE AND ATTITUDES OF COUPLES OF CHILDBEARING AGE IN CHOOSING CONTRACEPTION FOR MEN AT PMB NURHANETI, SOUTH JAKARTA FOR THE PERIOD NOVEMBER-DECEMBER 2023 - Setyaningsih, Vety; Sutarno, Maryati (HEARTY, 2025)
Background: Developing countries have various types of problems they face, one of which is the problem of high population growth rates, including Indonesia (Depkes, 2014). In 2017, Indonesia's population was 261,890.9 million. This population consisted of 133.17 million men and 131.88 million women (BPS, 2018). Among ASEAN countries, Indonesia is ranked 5th with a fertility rate or Total Fertility Rate (TFR) of 2.4. This figure is above the average TFR for ASEAN countries, namely 2.3 (World Population Data Sheet, 2019). Objective: To determine the relationship between knowledge and attitudes of couples of childbearing age in choosing contraception for men. Methods: quantitative research using a cross sectional design, data collection using questionnaires and data processing carried out univariate and bivariate with the Chi Square (X2) statistical test. Using 65 respondents of reproductive age couples with inclusion and exclusion criteria. Results: knowledge of couples of childbearing age, the results of the Chis-Square test analysis obtained a p value = 0.000, namely p value < α (0.000 < 0.05) which shows that there is a significant relationship between knowledge and male contraceptive choices, attitudes and the results of the analysis The Chis-Square test obtained a p value = 0.221, namely p value > α (0.221> 0.05) which shows that there is no significant relationship between attitudes and the choice of male contraception at PMB Nurhaneti, South Jakarta. Conclusions and Suggestions: knowledge can influence couples of childbearing age in choosing contraception for men, for health workers to be able to increase promotive efforts regarding.